ANALISIS PENGELOLAAN PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP MUHAMMADIYAH 57 MEDAN - Miftahul Jannah Lubis; Hasrian Rudi Setiawan (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This research aims to examine the management of the use of learning media in Islamic Religious Education subjects. This research was carried out at SMP Muhammadiyah 57 Medan. This research is a qualitative research method with data collection techniques used namely observation, interviews and documentation. The data analysis technique used is Miles and Huberman data analysis, namely data collection, data reduction, data presentation and drawing conclusions. To measure the validity of the data obtained, the author used triangulation. The results obtained in the research are that learning media management has several indicators starting from the planning, organizing and implementing stages of using learning media and media evaluation. PAI learning media developed at SMP Muhammadiyah 57 Medan consists of 2, namely visual and audio visual media. Learning media is arranged and adjusted for use. The learning media used by schools is also adequate, both visual media and audio-visual media. The implemention of learning media in learning received a good response.